Antimicrobial Resistance Mechanisms of Gram-Positive and Gram-Negative Bacteria - Xiao, Zhiwen (McGill Science Undergraduate Research Journal, 2024)
The discovery of antibiotics has long helped humans in the battle against bacteria. However, the misuse of antibiotics in industries and medical systems has unintentionally provided an ideal environment for bacteria to develop resistance mechanisms through mutations and gene transfer, resulting in the emergence of antimicrobial-resistant bacteria. This has proven to be an urgent and pressing issue in the global healthcare system, resulting in increased mortality. Therefore, increasing resources are invested to study their different resistance mechanisms and develop corresponding novel drugs and treatment methods. This review briefly introduces several key resistance mechanisms with examples from both Gram-negative and Gram-positive bacteria, the current and novel methods for treating multiple drug-resistant bacteria as well as the potential actions that could be done to improve the situation.